CEO Overconfidence and Dividend Payout Policy - Liu, Shijie (2022)
The payout policy depends on not only the company's development strategy but also the CEO's personal characteristics, and CEO overconfidence is one of the attributes that are widely discussed. This study investigates the impact of CEO overconfidence on dividend payout policy. We analyze the traditional dividend hypothesis, the irrational behaviors caused by CEO overconfidence, and how these irrational behaviors affect the payout policy.